2015
DOI: 10.1111/jon.12294
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Nerve Root Enhancement on MRI Scans in Children: A Review

Abstract: Spinal nerve root enhancement in pediatric patients is generally nonspecific, and clinical and laboratory correlation is essential. Nerve root enhancement indicates lack of integrity of the blood-nerve barrier. In this review, we will present a range of pediatric conditions that can present with spinal nerve root enhancement including inflammatory, infectious, hereditary, and neoplastic causes. Familiarity with the various pathologic entities associated with spinal nerve root enhancement is important for a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Although the study shows that these equivocal findings are unlikely to represent leptomeningeal CSF seeding, their significance at the time of tumor diagnosis and in the preoperative setting remains unclear. Diffuse, nonnodular cauda equina enhancement can be seen in a multitude of pediatric neurological diseases including inflammatory, infectious, hereditary, and neoplastic causes . Clumping of the cauda equina nerve roots reflects adhesions and is most commonly seen in the postoperative setting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the study shows that these equivocal findings are unlikely to represent leptomeningeal CSF seeding, their significance at the time of tumor diagnosis and in the preoperative setting remains unclear. Diffuse, nonnodular cauda equina enhancement can be seen in a multitude of pediatric neurological diseases including inflammatory, infectious, hereditary, and neoplastic causes . Clumping of the cauda equina nerve roots reflects adhesions and is most commonly seen in the postoperative setting.…”
mentioning
confidence: 99%
“…Diffuse, nonnodular cauda equina enhancement can be seen in a multitude of pediatric neurological diseases including inflammatory, infectious, hereditary, and neoplastic causes. 2 Clumping of the cauda equina nerve roots reflects adhesions and is most commonly seen in the postoperative setting. One possible explanation for these findings is an inflammatory response to circulating proteins or blood products, although this has not been proven.…”
mentioning
confidence: 99%
“…In retrospect, these changes were more suggestive of the presence of CMT1A, which has been previously reported to cause hypertrophic neuropathy due to concentric layers of myelin around degenerating axons caused by repeated cycles of myelination and demyelination producing the "onion bulb" appearance of the nerve on histologic examination, 5 even in patients with CMTD without prior radiation exposure. 6,15,16 To our knowledge, this is the first description of extensive cranial and nerve root enhancement and thickening on imaging of a pediatric patient with CMTD after radiotherapy and VCR exposure. Aghajan et al did report similar spinal MRI findings in a 16-year-old girl with previously undiagnosed CMTD; however, the patient had leptomeningeal disease at diagnosis and imaging was more consistent with tumor involvement of the spinal cord.…”
Section: Discussionmentioning
confidence: 88%
“…The contrast enhancement is usually more prominent in the anterior root of the spinal cord. 15 Although nonspecific, some recent studies have suggested serial contrast-enhanced MRI imaging as a useful tool to monitor the response to therapy. 16 In fact, persistent contrast enhancement was the motive to repeat the cycles of intravenous infusion of IVIG in our patient.…”
Section: Discussionmentioning
confidence: 99%